Support design during depillaring operation in bord and pillar panel using numerical simulation method - Hasim R.; Jaiswal A.; Shrivastva B.K. (My University, 2025)
In an underground coal mine, most successful and economical approach to support the underground structure is roof bolting technology. The most preferred method of working in Indian coal mine is Bord and Pillar. It has been observed from the past histories that, the maximum number of accidents happens during depillaring operation. In this paper, the primary focus is to understand and analyze the roof behavior with roof bolting system in underground coal mine using numerical simulation approach. A three-dimensional (3D) model of the depillaring panel with support design using roof bolt technology is complicated to simulate. Therefore, the simulation is done near the goaf edge, where maximum chances of roof failure have been observed. On another word, it can say that simulation is done before the main fall. An elasto – plastic model has been taken for study considering physico – mechanical properties, geo - mining condition, roof bolt and grout properties as an input parameter. A case of a depillaring panel of underground coal mine has been chosen for study. The result is observed regarding axial load exerted on the bolt during mine operation. Instrumented rock bolt data has been taken for validation of the model from field observation. It has been observed in the model that maximum axial load developed on the bolt is very close to the field observation. © 2017 AMSE Press. All Rights Reserved.